CORRELATION BETWEEN MUSCLE STRENGTH AND ENDURANCE WHEN USING SPECIALIZED FITNESS TRAINING FOR STUDENTS - P. Petkov (Trakia Journal of Sciences)
Testing was conducted during the winter semester of the academic 2016/2017 year. A total of 67 students from the Faculties of Agriculture, Veterinary Medicine and Economics at Trakia University, Stara Zagora, are the contingent of the survey. The average age of the surveyed students was 20.04 years. The aim of the study was to establish a correlation between muscle strength and endurance as a result of applying a specialized fitness model. To achieve this goal, the following tasks were assigned: review of scientific literature, development and approbation of a specialized fitness model, development of a test battery, processing and analysis of the data from the conducted testing. The following methods were applied: pedagogical experiment, testing and correlation analysis. Based on the conducted detailed correlation analysis, we believe that following the experimental fitness program, the relationships between muscle strength and stamina retain their essential characteristic - with a significant number of reliable statistical links; after the completion of the experiment, the statistically significant correlations of the EG increased. Significant increase with 99% statistical significance between motor skills after the application of the author's fitness model was observed; the conducted study showed different degrees of correlation dependencies between the motor skills muscle strength and stamina of the students.